1951
DOI: 10.1021/ja01149a056
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Ketene to Cyclic Conjugated Dienes

Abstract: The addition of ketene to cyclopentadiene and 1,3-cyclohexadiene has been found to afford unsaturated bicyclic ketones derived from bicyclo [3.2.0]heptane and bicyclo [4.2.0]octane, respectively. The saturated ketone derived from the ketenecyclopentadiene adduct yields e¿s-cyclopentane-l,2-dicarboxylic acid on oxidation. Complete reduction of the ketenecyclohexadiene adduct gave the previously described bicyclo [4.2.0]octane. A number of compounds containing the bicyclo-[3.2.0]heptane and bicyclo[4.2.0]octane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1956
1956
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Emphasis is placed on a comparison of the inhibitory ef- fects of these complexes on a water-catalyzed hydrolysis reaction. 5 The interpretation of the kinetic data is facilitated by results from conductivity studies.…”
mentioning
confidence: 99%
“…Emphasis is placed on a comparison of the inhibitory ef- fects of these complexes on a water-catalyzed hydrolysis reaction. 5 The interpretation of the kinetic data is facilitated by results from conductivity studies.…”
mentioning
confidence: 99%
“…However, it seems extremely unlikely that the ring juncture is trans fused, since Bloomfield has shown that this is unstable with respect to the ring-opened product under the reaction conditions. 4 Consistently, when a neat sample of 2 was heated in a sealed tube to 190 °C for 12 h no significant isomerization could be detected by ir, NMR, or GLC. It was similarly anticipated that the stereochemistry of the bicyclic esters would be maintained under the cyclization conditions and this was confirmed by spectral and chemical means.…”
Section: Resultsmentioning
confidence: 82%
“…have used this approach in an attempted asymmetric synthesis of aspartame. 20, 21 We realised that, in our case, a 5,5-disubstituted isoxazolidine (5) could be accessed by linking the cycloaddition components with a suitable tether (4). Intramolecular cycloaddition with a three-carbon tether should result in the diastereoselective formation of the cis-fused [3.3.0]isoxazolidine 5, according to a wealth of literature precedent.…”
Section: Introductionmentioning
confidence: 88%